Cutting tool

CN119604376APending Publication Date: 2025-03-11SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280098539.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2025-03-11

Smart Images

  • Figure CN119604376A_ABST
    Figure CN119604376A_ABST
Patent Text Reader

Abstract

A cutting tool provided with a base material and a coating film disposed on the base material, the coating film comprising a first layer comprising an alternating layer in which first unit layers and second unit layers are alternately laminated, the first unit layers comprising Ti1-a-bAlaCebN, a being 0.350-0.650 (inclusive), b being 0.001-0.100 (inclusive), and c being 0-0.5 (inclusive). The second unit layer is composed of AlcCr1-cN, c is from 0.40 to 0.75 (inclusive), and a and c satisfy cgt; and a.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to cutting tools. Background Art

[0002] Conventionally, a cutting tool including a substrate and a coating disposed on the substrate has been used for cutting processing (Patent Documents 1 and 2).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-64845

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 9-300105 Summary of the invention

[0007] A cutting tool according to one embodiment of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:

[0008] The coating comprises a first layer,

[0009] The first layer is composed of alternating layers in which first unit layers and second unit layers are alternately stacked.

[0010] The first unit layer is composed of Ti 1-a-b Al a Ce b N constitutes,

[0011] The value a is greater than or equal to 0.350 and less than or equal to 0.650.

[0012] b is greater than or equal to 0.001 and less than or equal to 0.100.

[0013] The second unit layer is composed of Al c Cr 1-c N constitutes,

[0014] The c is greater than or equal to 0.40 and less than or equal to 0.75.

[0015] The a and the c satisfy the relationship c>a.

[0016] A cutting tool according to another aspect of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:

[0017] The coating comprises a layer 1A,

[0018] The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked.

[0019] The first unit layer is composed of Ti 1-a-b Al aCe b N constitutes,

[0020] The value a is greater than or equal to 0.350 and less than or equal to 0.650.

[0021] b is greater than or equal to 0.001 and less than or equal to 0.100.

[0022] The third unit layer is composed of Al d Cr 1-d-e M e N constitutes,

[0023] The M is silicon or boron,

[0024] This d is greater than or equal to 0.40 and less than or equal to 0.75.

[0025] The value of e is greater than 0 and less than 0.05.

[0026] The a and the d satisfy the relationship of d>a. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic enlarged cross-sectional view of a cutting tool according to one embodiment of the present disclosure.

[0028] Figure 2 It is a schematic enlarged cross-sectional view of a cutting tool according to another embodiment of the present disclosure.

[0029] Figure 3 It is a schematic enlarged cross-sectional view of a cutting tool according to still another embodiment of the present disclosure.

[0030] Figure 4 It is a schematic enlarged cross-sectional view of a cutting tool according to still another embodiment of the present disclosure.

[0031] Figure 5 This is a diagram for explaining an example of the ratio of the thickness of the first unit layer to the thickness of the second unit layer.

[0032] Figure 6 It is a schematic cross-sectional view of a cathodic arc ion plating device used in Examples.

[0033] Figure 7 yes Figure 6 A schematic top view of a cathodic arc ion plating apparatus is shown. DETAILED DESCRIPTION

[0034] [Problems to be Solved by the Present Disclosure]

[0035] Cutting also plays a central role in manufacturing technology, and there is a constant demand for technological evolution and further sophistication. In cutting technology, high speed, high efficiency and high precision are basically required, but as a recent trend, there is a demand to respond to the difficulty of cutting materials. On this basis, in the field of cutting, in order to achieve a sustainable and better world by 2030, the attention to SDGs (Sustainable Development Goals) has been increasing in recent years. Here, sustainable development refers to the construction of a social foundation that can withstand the threat of nature without damaging the resources needed by future generations. For this reason, through the sophistication of cutting technology, it can be expected that the environmental load will be reduced by reducing the number of processes, saving electricity during product manufacturing, and reducing waste associated with cutting. If this situation is applied to cutting tools, in order to extend the life of the tool, it is directed to the development of various types of coated tool materials with high high temperature hardness and both hardness and toughness.

[0036] In the past, as a type of coated tool material, a nitride or carbonitride film with Ti and Al as the main components was coated on the surface of the substrate (Patent Document 1 and Patent Document 2). However, from the perspective of the aforementioned SDGs and the protection of the global environment, there is a tendency for the tip temperature of the cutting tool to become high during the cutting process due to reasons such as dry machining without using cutting oil, higher cutting speeds to improve machining efficiency, and diversification of cut materials, especially the increase in cutting of heat-resistant alloys and titanium alloys, which are called difficult-to-cut materials in the fields of aircraft and medicine. That is, if the tip temperature becomes high, the life of the cutting tool becomes extremely short. Therefore, a cutting tool that can show excellent tool life even under such harsh cutting conditions is required.

[0037] [Effects of the present disclosure]

[0038] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.

[0039] [Description of Embodiments of the Present Disclosure]

[0040] First, embodiments of the present disclosure will be described by way of examples.

[0041] (1) A cutting tool according to one aspect of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:

[0042] The coating comprises a first layer,

[0043] The first layer is composed of alternating layers formed by alternatingly stacking first unit layers and second unit layers,

[0044] The first unit layer is made of Ti 1-a-b Al a Ce b N constitutes,

[0045] a is greater than or equal to 0.350 and less than or equal to 0.650,

[0046] The b is greater than or equal to 0.001 and less than or equal to 0.100,

[0047] The second unit layer is made of Al c Cr 1-c N constitutes,

[0048] The c is greater than or equal to 0.40 and less than or equal to 0.75,

[0049] The a and the c satisfy the relationship c>a.

[0050] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.

[0051] (2) Preferably, in the above (1), in the first unit layer and the second unit layer adjacent to the first unit layer, a ratio λ2 / λ1 of a thickness λ2 of the second unit layer to a thickness λ1 of the first unit layer is greater than or equal to 1 and less than or equal to 5. Thus, in particular, in cutting processing performed under conditions where the tool tip temperature is high, a cutting tool having a longer tool life can be provided.

[0052] (3) Preferably, in the above (1) or (2), the average thickness of the first unit layer is 0.002 μm or more and 0.2 μm or less,

[0053] The average thickness of the second unit layer is 0.002 μm or more and 0.2 μm or less. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions where the tool tip temperature is high.

[0054] (4) Preferably, in any one of the above (1) to (3), the coating further includes a second layer disposed between the substrate and the first layer.

[0055] The composition of the second layer is the same as the composition of the first unit layer or the composition of the second unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0056] (5) Preferably, in the above (4), the composition of the second layer is the same as the composition of the first unit layer,

[0057] The thickness of the second layer is thicker than the thickness of the first unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under the condition of high tool tip temperature.

[0058] (6) Preferably, in the above (4), the composition of the second layer is the same as the composition of the second unit layer,

[0059] The thickness of the second layer is thicker than the thickness of the second unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under the condition of high tool tip temperature.

[0060] (7) Preferably, in any one of the above (1) to (6), the coating further includes a third layer provided on the side of the first layer opposite to the substrate,

[0061] The third layer is composed of TiAlCeCN. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0062] (8) A cutting tool according to another aspect of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:

[0063] The coating comprises a layer 1A,

[0064] The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked.

[0065] The first unit layer is made of Ti 1-a-b Al a Ce b N constitutes,

[0066] a is greater than or equal to 0.350 and less than or equal to 0.650,

[0067] The b is greater than or equal to 0.001 and less than or equal to 0.100,

[0068] The third unit layer is composed of Al d Cr 1-d-e M e N constitutes,

[0069] The M is silicon or boron,

[0070] The d is greater than or equal to 0.40 and less than or equal to 0.75,

[0071] The e is greater than 0 and less than 0.05,

[0072] The a and the d satisfy the relationship of d>a.

[0073] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.

[0074] (9) Preferably, in the above (8), in the first unit layer and the third unit layer adjacent to the first unit layer, a ratio λ3 / λ1 of a thickness λ3 of the third unit layer to a thickness λ1 of the first unit layer is greater than or equal to 1 and less than or equal to 5. Thus, in particular, in cutting processing performed under conditions where the tool tip temperature is high, a cutting tool having a longer tool life can be provided.

[0075] (10) Preferably, in the above (8) or (9), M is silicon. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0076] (11) Preferably, in the above (8) or (9), M is boron. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0077] (12) Preferably, in any one of the above (8) to (11), the average thickness of the first unit layer is 0.002 μm or more and 0.2 μm or less,

[0078] The average thickness of the third unit layer is 0.002 μm or more and 0.2 μm or less. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions where the tool tip temperature is high.

[0079] (13) Preferably, in any one of the above (8) to (12), the coating further includes a second layer disposed between the substrate and the 1A layer.

[0080] The composition of the second layer is the same as the composition of the first unit layer or the composition of the third unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0081] (14) Preferably, in the above (13), the composition of the second layer is the same as the composition of the first unit layer,

[0082] The thickness of the second layer is thicker than the thickness of the first unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under the condition of high tool tip temperature.

[0083] (15) Preferably, in the above (13), the composition of the second layer is the same as the composition of the third unit layer,

[0084] The thickness of the second layer is thicker than the thickness of the third unit layer. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under the condition of high tool tip temperature.

[0085] (16) Preferably, in any one of the above (8) to (15), the coating further includes a third layer provided on the side of the 1A layer opposite to the substrate,

[0086] The third layer is composed of TiAlCeCN. Thus, a cutting tool having a longer tool life can be provided, especially in cutting processing performed under conditions of high tool tip temperature.

[0087] [Details of the embodiments of the present disclosure]

[0088] Hereinafter, a specific example of a cutting tool according to an embodiment of the present disclosure (hereinafter, also referred to as "the present embodiment") will be described with reference to the accompanying drawings. In the drawings of the present disclosure, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.

[0089] In this specification, expressions in the form of "A to B" refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.

[0090] In this specification, when a compound is represented by a chemical formula, when the atomic ratio is not particularly limited, all conventionally known atomic ratios are included, and it is not necessarily limited to the atomic ratio within the stoichiometric range. For example, when it is described as "TiAlCeN", the ratio of the number of atoms constituting TiAlCeN includes all conventionally known atomic ratios.

[0091] [Embodiment 1: Cutting tool (1)]

[0092] use Figure 1 to Figure 5 A cutting tool according to an embodiment of the present disclosure will be described.

[0093] One embodiment of the present disclosure (hereinafter also referred to as “Embodiment 1”) is a cutting tool 1 including a substrate 2 and a coating 3 disposed on the substrate 2, wherein:

[0094] The coating 3 comprises first layers 13, 13',

[0095] The first layers 13, 13' are composed of alternating layers formed by alternately stacking the first unit layers 12 and the second unit layers 15.

[0096] The first unit layer 12 is made of Ti 1-a-b Al a Ce b N constitutes,

[0097] The value a is greater than or equal to 0.350 and less than or equal to 0.650.

[0098] b is greater than or equal to 0.001 and less than or equal to 0.100.

[0099] The second unit layer 15 is made of Al c Cr 1-c N constitutes,

[0100] The c is greater than or equal to 0.40 and less than or equal to 0.75.

[0101] The a and the c satisfy the relationship c>a.

[0102] According to the present disclosure, it is possible to provide a cutting tool 1 having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high in particular. The reason for this is presumably as follows.

[0103] (a) In the above-mentioned cutting tool 1, the coating 3 includes the first layer 13, 13', and the first layer 13, 13' is composed of alternating layers formed by alternately stacking the first unit layer 12 and the second unit layer 15. As a result, in the first layer, the "crack resistance" and "oxidation resistance" of the first layer 13, 13' can be improved due to the reduction of grain boundaries, and the "progress of cracks" can be suppressed at the interface between the first unit layer 12 and the second unit layer 15.

[0104] (b) As described above, the coating 3 includes the first layers 13 and 13', which are composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked. 1-a-b Al a Ce b N, the second unit layer 15 is composed of Al c Cr 1-c N. With Al c Cr 1-c Compared with N, Ti 1-a-b Al a Ce b N is not prone to spinodal decomposition at high temperatures. Therefore, in the first unit layer 12, there is a tendency that the hardness decreases and the compressive residual stress increases, and the crack resistance is excellent. On the other hand, compared with Ti 1-a-b Al a Ce b Compared with N, Al c Cr 1-cN has a tendency to have a small compressive residual stress and excellent "thermal blocking property" (in other words, "heat resistance"). Since the first layer 13, 13' is alternately stacked with the first unit layer 12 and the second unit layer 15, it has both the high "hardness" of the first unit layer 12 and the excellent "heat resistance" of the second unit layer 15, and the small compressive residual stress of the second unit layer 15 is supplemented by the large compressive residual stress of the first unit layer 12. Therefore, as a whole, the first layer 13, 13' can improve the hardness, heat resistance and compressive residual stress in a balanced manner.

[0105] (c) In the cutting tool 1, the first unit layer 12 is made of Ti 1-a-b Al a Ce b N, a is greater than or equal to 0.350 and less than or equal to 0.650, and b is greater than or equal to 0.001 and less than or equal to 0.100. As a result, Al is easily oxidized, and thus a dense oxide layer composed of Al2O3 is easily formed on the surface side of the first unit layer 12. Furthermore, Ce has a smaller standard generation energy of oxide than Al, and thus is more easily oxidized than Al, and a dense oxide layer composed of CeO2 is easily formed on the outermost surface of the first unit layer 12. Through these oxide layers, the "oxidation resistance" of the coating 3 is improved, and the reactivity with the cut material can be suppressed, and the friction coefficient with the cut material can be reduced. In addition, the lattice constant of CeN is Larger than the lattice constant of TiN Lattice constant of AlN Therefore, strain is introduced into the first cell layer 12, and the structure of the first cell layer 12 is refined. As a result, the hardness of the first cell layer 12 is increased, so that the "wear resistance" of the first cell layer 12 can be improved.

[0106] (d) In the cutting tool 1, the first unit layer 12 is made of Ti 1-a-b Al a Ce b N, ... the second unit layer 15 is composed of Al c Cr 1-c N, ... a and c satisfy the relationship of c>a. Since the difference between the lattice constant of AlN and CrN in the second unit layer 15 is smaller than the difference between the lattice constant of TiN and AlN in the first unit layer 12, the second unit layer 15 tends to have a higher Al content than the first unit layer 12. Therefore, by increasing the Al content in the second unit layer 15, the Al content contained in the first layer 13, 13' as a whole can be increased. As a result, the "heat resistance" and "oxidation resistance" of the first layer 13, 13' can be improved.

[0107] That is, according to the present disclosure, the cutting tool 1 can have excellent "crack resistance", excellent "oxidation resistance", excellent "crack progression inhibition effect", high "hardness", excellent "wear resistance", and excellent "heat resistance", so especially in cutting processing performed under conditions of high tip temperature, a cutting tool 1 with a longer tool life can be provided.

[0108] Cutting Tools

[0109] like Figure 1 As shown, a cutting tool 1 involved in one embodiment of the present disclosure comprises a substrate 2 and a coating 3 arranged on the substrate 2. The coating 3 preferably covers the entire surface of the substrate 2, but even if a portion of the substrate 2 is not covered by the coating 3, or the composition of the coating 3 is partially different, it does not deviate from the scope of the present embodiment. In the case where a portion of the substrate 2 is not covered by the coating 3, the coating 3 is preferably arranged in a manner that covers the surface of at least the portion of the substrate 2 that participates in cutting. In this specification, the portion of the substrate 2 that participates in cutting also depends on the size and shape of the substrate 2, but in the substrate 2, it refers to an area surrounded by an imaginary surface whose distance from the blade edge line and the perpendicular line of the tangent along the blade edge line from the blade edge line to the substrate 2 side is any one of 5 mm, 3 mm, 2 mm, 1 mm, and 0.5 mm.

[0110] The cutting tool 1 of this embodiment can be suitably used as a cutting tool 1 such as a drill, an end mill, an indexable cutting insert for a drill, an indexable cutting insert for an end mill, an indexable cutting insert for milling, an indexable cutting insert for turning, a metalworking saw, a gear cutting tool, a reamer, and a tap.

[0111] <Base Material>

[0112] As the substrate 2, any substrate can be used as long as it is a substrate that is conventionally known as such a substrate 2. For example, preferably any one of cemented carbide (WC-based cemented carbide, cemented carbide containing WC and Co, cemented carbide to which carbonitrides such as Ti, Ta, and Nb are added, etc.), cermet (cermet containing TiC, TiN, TiCN, etc. as the main component), high-speed steel, ceramic (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cubic boron nitride sintered body, or diamond sintered body.

[0113] Among these various substrates 2, WC-based cemented carbide and cermet (especially TiCN-based cermet) are particularly preferably selected. These substrates 2 have an excellent balance between hardness and strength, especially at high temperatures, and therefore, when used as the substrate 2 of the cutting tool 1, they can contribute to the long life of the cutting tool 1.

[0114] <Lamination>

[0115] The coating 3 of the first embodiment includes the first layer 13, 13'. The coating 3 has the function of improving the wear resistance, chipping resistance and other characteristics of the cutting tool 1 and extending the life of the cutting tool 1 by covering the substrate 2. In addition, the coating 3 may include "other layers" described later in addition to the first layer 13, 13'.

[0116] The overall thickness of the coating 3 is preferably not less than 0.5 μm and not more than 15 μm. If the overall thickness is less than 0.5 μm, the coating 3 is too thin, and there is a tendency for the life of the cutting tool 1 to be shortened. On the other hand, if the overall thickness exceeds 15 μm, the coating 3 is prone to cracking at the beginning of cutting, and there is a tendency for the life of the cutting tool 1 to be shortened. The overall thickness of the coating 3 can be measured by observing the cross section of the coating 3 using an SEM (scanning electron microscope). Specifically, the observation magnification of the cross-section sample is set to 5000 to 10000 times, and the observation area is set to 100 to 500 μm. 2 The thickness widths at three locations in one field of view are measured, and the average value is defined as the “thickness.” The thickness of each layer described below is similar unless otherwise specified.

[0117] The absolute value of the compressive residual stress of the coating 3 is preferably 6 GPa or less. The compressive residual stress of the coating 3 refers to a type of internal stress (intrinsic strain) present in the entire coating 3, and refers to a stress expressed by a "-" (negative) numerical value (unit: "GPa" is used in this embodiment). Therefore, the concept of a large compressive residual stress means that the absolute value of the numerical value becomes larger, and the concept of a small compressive residual stress means that the absolute value of the numerical value becomes smaller. That is, the absolute value of the compressive residual stress is 6 GPa or less, which means that the preferred compressive residual stress associated with the coating 3 is greater than -6 GPa and less than 0 GPa.

[0118] If the compressive residual stress of the coating 3 exceeds 0 GPa, it becomes a tensile stress, so there is a tendency that it is difficult to suppress the progress of cracks generated from the outermost surface of the coating 3. On the other hand, if the absolute value of the compressive residual stress exceeds 6 GPa, there is a risk that the stress is too high, and the coating 3 peels off, especially from the edge of the cutting tool 1, before cutting starts, and the life of the cutting tool 1 is shortened.

[0119] The compressive residual stress of the coating 3 can be measured by the sin2ψ method using an X-ray residual stress apparatus (see pages 54 to 66 of "X-ray Stress Measurement Method" (Japan Materials Society, published by Yokendo Co., Ltd. in 1981)).

[0120] The crystal structure of the coating 3 is preferably a cubic crystal. If the crystal structure of the coating 3 is a cubic crystal, the hardness of the coating 3 is improved. Therefore, the crystal structure of each layer in the coating 3 is preferably a cubic crystal. In addition, the crystal structure of the coating 3 and each layer in the coating 3 can be analyzed by an X-ray diffraction device known in the art.

[0121] The hardness of the coating 3 is preferably 30 GPa or more and 55 GPa or less, and more preferably 35 GPa or more and 50 GPa or less. Thus, the coating 3 has sufficient hardness. In addition, the hardness of the entire coating 3 can be measured using a nano indenter method (Nano Indenter XP manufactured by MTS). Specifically, the method according to ISO14577 is used, the measurement load is set to 10 mN (1 gf), and the hardness of three locations on the surface of the coating 3 is measured, and the average value is used as the "hardness".

[0122] <First Floor>

[0123] The first layers 13 and 13' of the present embodiment are composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked. As a result, the "crack resistance" and "oxidation resistance" of the first layers 13 and 13' can be improved, and the "progress of cracks" can be suppressed at the interface between the first unit layers 12 and the second unit layers 15, so the "crack resistance" and "oxidation resistance" of the coating 3 can be improved, and the "progress of cracks" of the coating 3 can be suppressed. In addition, the fact that "the first layers 13 and 13' are composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked" can be confirmed by observing the cross section of the coating 3 using a TEM (transmission electron microscope) and the difference in contrast.

[0124] The thickness of the first layer 13, 13' is preferably 0.5 μm to 15 μm. If the thickness of the first layer 13, 13' is less than 0.5 μm, the wear resistance may not be fully exhibited in continuous processing, while if the thickness exceeds 15 μm, the chipping resistance may be difficult to stabilize in intermittent cutting.

[0125] The thickness of the first layer 13, 13' can be determined by observing and measuring the cross section of the coating 3 using a TEM (transmission electron microscope). Specifically, the sample after thinning is irradiated with an electron beam, and the electrons that pass through the sample and the scattered electrons are imaged and observed at a high magnification, so that the thickness of the first layer 13, 13' can be measured.

[0126] (Composition of the first unit layer and composition of the second unit layer)

[0127] The first unit layer 12 is made of Ti 1-a-b Al aCe b N composition, a is greater than or equal to 0.350 and less than or equal to 0.650, and b is greater than or equal to 0.001 and less than or equal to 0.100. Thus, the "oxidation resistance" and "wear resistance" of the coating 3 can be improved. The a is preferably greater than or equal to 0.400, more preferably greater than or equal to 0.450, and further preferably greater than or equal to 0.500. The a is preferably less than or equal to 0.650, more preferably less than or equal to 0.600, and further preferably less than or equal to 0.550. The a is preferably greater than or equal to 0.400 and less than or equal to 0.650, more preferably greater than or equal to 0.450 and less than or equal to 0.600, and further preferably greater than or equal to 0.500 and less than or equal to 0.055. The b is preferably greater than or equal to 0.005, more preferably greater than or equal to 0.01, and further preferably greater than or equal to 0.015. The b is preferably less than or equal to 0.070, more preferably less than or equal to 0.050, and further preferably less than or equal to 0.020. The value of b is preferably 0.005 or more and 0.050 or less, more preferably 0.007 or more and 0.030 or less, and still more preferably 0.010 or more and 0.020 or less. 1-a-b Al a Ce b N structure" means that as long as the effect of the present disclosure is exhibited, 1-a-b Al a Ce b In addition to N, it may also contain inevitable impurities. Examples of the inevitable impurities include oxygen and carbon. The overall content of the inevitable impurities in the first unit layer 12 is preferably greater than 0 atomic % and less than 1 atomic %. Here, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms constituting the layer. The ratio (%) of the number of atoms to the total number of atoms constituting the layer is calculated by the same method as the "measurement method of a and b" described later. In addition, it was confirmed that as long as the measurement is performed in the same cutting tool 1, there is no deviation in the measurement result even if the measurement site is arbitrarily selected.

[0128] The above-mentioned a and b are obtained by elemental analysis based on transmission electron microscope (TEM) observation of the sample cross section. Specifically, the energy and the number of characteristic X-rays generated when the sample after thinning the thin film cross section is irradiated with an electron beam are measured using EDS (Energy Dispersive X-ray Spectroscopy) attached to the TEM, and elemental analysis is performed to obtain them. In addition, the following situation is confirmed: as long as the measurement is performed on the same cutting tool 1, there is no deviation in the measurement result even if the measurement position is arbitrarily selected.

[0129] The second unit layer 15 is made of Al c Cr 1-cN. As a result, due to the excellent balance between the heat resistance and the oxidation resistance and toughness of AlCrN, the coating 3 can have excellent heat resistance, oxidation resistance and toughness. c Cr 1-c N structure" means that as long as the effect of the present disclosure is exhibited, c Cr 1- c In addition to N, it may also contain inevitable impurities. Examples of the inevitable impurities include oxygen and carbon. The overall content of the inevitable impurities in the second unit layer 15 is preferably greater than 0 atomic % and less than 1 atomic %. Here, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms constituting the layer. The ratio (%) of the number of atoms to the total number of atoms constituting the layer is calculated by the same method as the above-mentioned "measurement method of a and b". In addition, the following was confirmed: as long as the measurement is performed in the same cutting tool 1, there is no deviation in the measurement result even if the measurement site is arbitrarily selected.

[0130] The c is greater than or equal to 0.40 and less than or equal to 0.75. As a result, the crystal structure of the second unit layer 15 becomes a cubic crystal, and the second unit layer 15 has a high hardness. As a result, the "wear resistance" of the second unit layer 15 is improved. The c is preferably greater than or equal to 0.50, more preferably greater than or equal to 0.55, and further preferably greater than or equal to 0.60. The c is preferably less than or equal to 0.75, more preferably less than or equal to 0.70, and further preferably less than or equal to 0.65. The c is preferably greater than or equal to 0.50 and less than or equal to 0.75, more preferably greater than or equal to 0.55 and less than or equal to 0.70, and further preferably greater than or equal to 0.60 and less than or equal to 0.65.

[0131] The above c is obtained by the same method as the measurement method of the above a and the above b. In addition, it was confirmed that as long as the measurement is performed on the same cutting tool 1, there is no variation in the measurement result even if the measurement position is arbitrarily selected.

[0132] The above-mentioned a and the above-mentioned c satisfy the relationship of c>a. Thereby, the “heat resistance” and “oxidation resistance” of the coating 3 can be improved.

[0133] (Average thickness of the first unit layer and average thickness of the second unit layer)

[0134] The average thickness of the first unit layer 12 is preferably 0.002 μm or more and 0.2 μm or less, and the average thickness of the second unit layer 15 is preferably 0.002 μm or more and 0.2 μm or less. Thus, the progress of cracks generated on the surface of the coating 3 can be further suppressed. The lower limit of the average thickness of the first unit layer 12 is preferably 0.002 μm or more, more preferably 0.005 μm or more, and more preferably 0.01 μm or more. The upper limit of the average thickness of the first unit layer 12 is preferably 0.2 μm or less, more preferably 0.15 μm or less, and more preferably 0.1 μm or less. The average thickness of the first unit layer 12 is more preferably 0.005 μm or more and 0.15 μm or less, and more preferably 0.01 μm or more and 0.1 μm or less. The lower limit of the average thickness of the second unit layer 15 is preferably 0.002 μm or more, more preferably 0.005 μm or more, and more preferably 0.01 μm or more. The upper limit of the average thickness of the second unit layer 15 is preferably 0.2 μm or less, more preferably 0.15 μm or less, and further preferably 0.1 μm or less. The average thickness of the second unit layer 15 is more preferably 0.005 μm to 0.15 μm, and further preferably 0.01 μm to 0.1 μm.

[0135] The average thickness of the first unit layer 12 and the average thickness of the second unit layer 15 can be determined by the same method as the method for measuring the thickness of the first layers 13 and 13 ′ described above.

[0136] In the first unit layer 12 and the second unit layer 15 adjacent to the first unit layer 12, the ratio λ2 / λ1 of the thickness λ2 of the second unit layer 15 to the thickness λ1 of the first unit layer 12 is preferably 1 or more and 5 or less ( Figure 5 ). Since the "thermal conductivity" of the second unit layer 15 is low, the second unit layer 15 has the property of being difficult to transfer the heat generated during cutting to the substrate 2. Therefore, if the proportion of the second unit layer 15 in the first layer 13, 13' is relatively increased, the amount of Al in the coating 3 increases, thereby improving the thermal blocking property (in other words, "heat resistance") of the cutting tool 1 as a whole, so that the "wear resistance" can also be improved, especially in cutting processing performed under conditions of high tip temperature. λ2 / λ1 is preferably greater than 1, more preferably greater than 1.5, and further preferably greater than 2. λ2 / λ1 is preferably less than 5, more preferably less than 4, and further preferably less than 3. λ2 / λ1 is preferably greater than 1 and less than 5, more preferably greater than 1.5 and less than 4, and further preferably greater than 2 and less than 3.

[0137] In the first layer 13, 13', the stacking number of the first unit layer 12 and the second unit layer 15 is preferably 10 or more and 500 or less. As a result, there is a tendency to easily obtain the effect of "balanced improvement of hardness and compressive residual stress by stacking the first unit layer 12 and the second unit layer 15". In the first layer 13, 13', the stacking number of the first unit layer 12 and the second unit layer 15 is more preferably 100 or more and 400 or less, and further preferably 200 or more and 350 or less.

[0138] In the first layer 13, 13', the stacking number of the first unit layer 12 and the second unit layer 15 can be determined by observing and measuring the cross section of the coating 3 using a TEM (transmission electron microscope). Specifically, the sample after being sliced ​​is irradiated with an electron beam, and the electrons that pass through the sample and the scattered electrons are imaged and observed at a high magnification, so that the stacking number of the first unit layer 12 and the second unit layer 15 can be measured.

[0139] <Other layers>

[0140] As other layers, for example, the second layer 16 ( Figure 3 , Figure 4 ), the third layer 14 ( Figure 1 to Figure 4 ) etc. In addition, the coating 3 may further include an intermediate layer (not shown) between the second layer 16 and the first layer 13 , 13 ′, or between the first layer 13 , 13 ′ and the third layer 14 .

[0141] (Second floor)

[0142] The coating 3 further includes a second layer 16 disposed between the substrate 2 and the first layers 13, 13'. The composition of the second layer 16 is preferably the same as the composition of the first unit layer 12 or the composition of the second unit layer 15 ( Figure 3 as well as Figure 4 ). Thus, the adhesion between the substrate 2 and the coating 3 can be improved.

[0143] Furthermore, when the composition of the second layer 16 is the same as that of the first unit layer 12 , even if the substrate 2 is exposed at the initial stage of cutting, oxidation at the interface between the substrate 2 and the coating 3 can be suppressed.

[0144] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is preferably thicker than that of the first unit layer 12. Thus, the close contact between the substrate 2 and the coating 3 can be further improved. In addition, even if the substrate 2 is exposed at the initial stage of cutting, oxidation from the interface between the substrate 2 and the coating 3 can be further suppressed. In addition, "the thickness of the second layer 16 is thicker than the thickness of the first unit layer 12" can be said to be "the thickness of the second layer 16 exceeds 1.0 times the thickness of the first unit layer 12". The thickness of the second layer 16 is preferably 2.0 times or more of the thickness of the first unit layer 12, more preferably 4.0 times or more, and further preferably 10.0 times or more. The thickness of the second layer 16 is preferably 500 times or less of the thickness of the first unit layer 12, more preferably 120 times or less, and further preferably 50 times or less. The thickness of the second layer 16 is preferably 2.0 times or more and 500 times or less, more preferably 4.0 times or more and 120 times or less, and further preferably 10.0 times or more and 50 times or less, the thickness of the first unit layer 12 .

[0145] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is preferably 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it is difficult to obtain the effect of suppressing oxidation from the interface between the substrate 2 and the coating 3 by setting the second layer 16 to the same composition as the first unit layer 12. When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is more preferably 0.3 μm or more, and further preferably 0.4 μm or more. In addition, the upper limit of the thickness of the second layer 16 is not particularly limited, but if it is greater than 2 μm, the grains are enlarged and grain boundaries are generated, thereby there is a tendency to be difficult to further improve the above-mentioned oxidation suppression effect. Therefore, considering the cost aspect, the thickness of the second layer 16 is preferably 2 μm or less.

[0146] When the composition of the second layer 16 is the same as that of the first unit layer 12, the first unit layer 12 of the first layer 13, 13' can be stacked immediately above the second layer 16 having the same composition as that of the first unit layer 12. Figure 4 ), and in addition, a second unit layer 15 ( Figure 3 ). In addition, when the composition of the second layer 16 is the same as that of the first unit layer 12, and the first unit layer 12 of the first layer 13, 13' is stacked immediately above the second layer 16, the second layer 16 and the first unit layer 12 of the first layer 13, 13' have a continuous crystal structure.

[0147] When the composition of the second layer 16 is the same as that of the second unit layer 15, the second unit layer 15 tends to have a small stress, so the peeling resistance of the coating 3 can be improved, especially in intermittent processing such as milling and end milling where loads are repeatedly applied to the tool tip.

[0148] When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 is preferably thicker than that of the second unit layer 15. As a result, the peeling resistance of the coating 3 can be further improved, especially in intermittent processing such as milling processing and end mill processing in which a load is repeatedly applied to the tool tip. In addition, "the thickness of the second layer 16 is thicker than the thickness of the second unit layer 15" can be said to be "the thickness of the second layer 16 exceeds 1.0 times the thickness of the second unit layer 15". The thickness of the second layer 16 is preferably 2.0 times or more, more preferably 4.0 times or more, and further preferably 10.0 times or more of the thickness of the second unit layer 15. The thickness of the second layer 16 is preferably 500 times or less, more preferably 120 times or less, and further preferably 50 times or less of the thickness of the second unit layer 15. The thickness of the second layer 16 is preferably 2.0 times or more and 500 times or less, more preferably 4.0 times or more and 120 times or less, and further preferably 10.0 times or more and 50 times or less, the thickness of the second unit layer 15 .

[0149] When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 is preferably 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it tends to be difficult to obtain the effect of improving the peeling resistance by setting the second layer 16 to the same composition as the second unit layer 15. When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 is more preferably 0.3 μm or more, and further preferably 0.4 μm or more. In addition, the upper limit of the thickness of the second layer 16 is not particularly limited, but if it is greater than 2 μm, there is a tendency that the above-mentioned further improvement in peeling resistance cannot be confirmed. Therefore, considering the cost aspect, the thickness of the second layer 16 is preferably 2 μm or less.

[0150] When the composition of the second layer 16 is the same as that of the second unit layer 15, the first unit layer 12 of the first layer 13, 13' can be stacked immediately above the second layer 16 having the same composition as that of the second unit layer 15. Figure 4 ), and in addition, a second unit layer 15 ( Figure 3 ). In addition, when the composition of the second layer 16 is the same as that of the second unit layer 15, and the second unit layer 15 of the first layer 13, 13' is stacked immediately above the second layer 16, the second layer 16 and the second unit layer 15 of the first layer 13, 13' have a continuous crystal structure.

[0151] (Third floor)

[0152] The coating 3 further includes a third layer 14 disposed on the side of the first layer 13, 13' opposite to the substrate 2. The third layer 14 is preferably composed of TiAlCeCN ( Figure 1 to Figure 4 ). As a result, the friction coefficient of the coating 3 can be reduced, thereby extending the life of the cutting tool 1.

[0153] Generally speaking, carbonitrides tend to have a lower friction coefficient with respect to the cut material than nitrides. It is believed that such a reduction in the friction coefficient is due to the contribution of carbon atoms. If the coating 3 includes the third layer 14, the friction coefficient of the coating 3 with respect to the cut material is reduced, and the life of the cutting tool 1 is extended.

[0154] The third layer 14 can be given a predetermined color by adjusting the composition ratio of N and C. This can impart design and recognition properties to the appearance of the cutting tool 1, which is commercially useful.

[0155] The thickness of the third layer 14 is preferably 0.1 μm or more. If the thickness of the third layer 14 is less than 0.1 μm, it is sometimes difficult to obtain the lubricity imparting effect brought by the third layer 14. On the other hand, the upper limit of the thickness of the third layer 14 is not particularly limited, but if it is greater than 2 μm, there is a tendency that the above-mentioned lubricity imparting effect cannot be further improved. Therefore, considering the cost aspect, the thickness of the third layer 14 is preferably 2 μm or less.

[0156] (Middle layer)

[0157] The intermediate layer is a layer disposed between the second layer 16 and the first layer 13, 13', or between the first layer 13, 13' and the third layer 14. Examples of the intermediate layer include TiAlCeN, AlCrN, AlCrBN, AlCrSiN, etc. The thickness of the intermediate layer can be set to 0.1 μm to 2 μm, 0.3 μm to 1.5 μm, or 0.4 μm to 1.0 μm.

[0158] [Embodiment 2: Cutting tool (2)]

[0159] use Figure 1 to Figure 5 , a cutting tool according to another embodiment of the present disclosure is described.

[0160] Another embodiment of the present disclosure (hereinafter also referred to as “Embodiment 2”) is a cutting tool comprising a substrate and a coating disposed on the substrate, wherein:

[0161] The coating comprises a layer 1A,

[0162] The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked.

[0163] The first unit layer is composed of Ti 1-a-b Al a Ce b N constitutes,

[0164] The value a is greater than or equal to 0.350 and less than or equal to 0.650.

[0165] b is greater than or equal to 0.001 and less than or equal to 0.100.

[0166] The third unit layer is composed of Al d Cr 1-d-e M e N constitutes,

[0167] The M is silicon or boron,

[0168] This d is greater than or equal to 0.40 and less than or equal to 0.75.

[0169] The value of e is greater than 0 and less than 0.05.

[0170] The a and the d satisfy the relationship of d>a.

[0171] In the cutting tool 1 of embodiment 2, except for the following structure, the same structure as embodiment 1 is adopted, that is, "the coating 3 includes "1A layer 13, 13'", "the composition of the second layer 16 is preferably the same as the composition of the first unit layer 12 or the composition of the "third unit layer 17", and "preferably, the coating 3 also includes a third layer 14 arranged on the side of the "1A layer 13, 13'" opposite to the substrate 2, and the third layer 14 is composed of TiAlCeCN". The following describes the "1A layer 13, 13'" and the "second layer".

[0172] <1A Floor>

[0173] The 1A layers 13 and 13' of the present embodiment are composed of alternating layers in which the first unit layer 12 and the third unit layer 17 are alternately stacked. As a result, the "crack resistance" and "oxidation resistance" of the 1A layers 13 and 13' can be improved, and the "progress of cracks" can be suppressed at the interface between the first unit layer 12 and the third unit layer 17, so the "crack resistance" and "oxidation resistance" of the coating 3 can be improved, and the "progress of cracks" of the coating 3 can be suppressed. In addition, the fact that "the 1A layers 13 and 13' are composed of alternating layers in which the first unit layer 12 and the third unit layer 17 are alternately stacked" can be confirmed by observing the cross section of the coating 3 using a TEM (transmission electron microscope) and the difference in contrast.

[0174] The thickness of the first A layer 13, 13' is preferably 0.5 μm to 15 μm. If the thickness of the first A layer 13, 13' is less than 0.5 μm, the wear resistance may not be fully exhibited in continuous processing, while if the thickness is greater than 15 μm, the chipping resistance may be difficult to stabilize in intermittent cutting.

[0175] The thickness of the first A layer 13, 13' can be determined by observing and measuring the cross section of the coating 3 using a TEM (transmission electron microscope). Specifically, the sample after thinning is irradiated with an electron beam, and the electrons that pass through the sample and the scattered electrons are imaged and observed at a high magnification, so that the thickness of the first A layer 13, 13' can be measured.

[0176] (Composition of the first unit layer and composition of the third unit layer)

[0177] The first unit layer 12 is made of Ti 1-a-b Al a Ce b N composition, a is greater than or equal to 0.350 and less than or equal to 0.650, and b is greater than or equal to 0.001 and less than or equal to 0.100. Thus, the "oxidation resistance" and "wear resistance" of the coating 3 can be improved. The a is preferably greater than or equal to 0.400, more preferably greater than or equal to 0.450, and further preferably greater than or equal to 0.500. The a is preferably less than or equal to 0.640, more preferably less than or equal to 0.600, and further preferably less than or equal to 0.550. The a is preferably greater than or equal to 0.400 and less than or equal to 0.650, more preferably greater than or equal to 0.450 and less than or equal to 0.600, and further preferably greater than or equal to 0.500 and less than or equal to 0.550. The b is preferably greater than or equal to 0.005, more preferably greater than or equal to 0.007, and further preferably greater than or equal to 0.010. The b is preferably less than or equal to 0.070, more preferably less than or equal to 0.050, and further preferably less than or equal to 0.020. The value of b is preferably 0.005 or more and 0.050 or less, more preferably 0.007 or more and 0.030 or less, and still more preferably 0.010 or more and 0.020 or less. 1-a-b Al a Ce b N structure" means that as long as the effect of the present disclosure is exhibited, 1-a-b Al a Ce bIn addition to N, it may also contain inevitable impurities. Examples of the inevitable impurities include oxygen and carbon. The overall content of the inevitable impurities in the first unit layer 12 is preferably greater than 0 atomic % and less than 1 atomic %. Here, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms constituting the layer. The ratio (%) of the number of atoms to the total number of atoms constituting the layer is calculated by the same method as the "measurement method of a and b" described later. In addition, it was confirmed that as long as the measurement is performed in the same cutting tool 1, there is no deviation in the measurement result even if the measurement site is arbitrarily selected.

[0178] The above-mentioned a and b are obtained by elemental analysis based on transmission electron microscope (TEM) observation of the sample cross section. Specifically, the energy and the number of characteristic X-rays generated when the sample after thinning the thin film cross section is irradiated with an electron beam are measured using EDS (Energy Dispersive X-ray Spectroscopy) attached to the TEM, and elemental analysis is performed to obtain them. In addition, it is confirmed that as long as the measurement is performed on the same cutting tool 1, there is no deviation in the measurement result even if the measurement position is arbitrarily selected.

[0179] The third unit layer 17 is made of Al d Cr 1-d-e M e N is composed of silicon or boron. As a result, the third unit layer 17 can have both excellent hardness and excellent oxidation resistance. The mechanism is not yet clear in detail, but it is estimated to be as follows.

[0180] When M is boron, the hardness of the third unit layer 17 increases due to boron, and the hardness of the entire coating 3 increases. In addition, the boron oxide formed by oxidation of the surface of the cutting tool 1 accompanying cutting densifies the Al oxide in the third unit layer 17, and as a result, the oxidation resistance of the third unit layer 17 is improved. Furthermore, since the boron oxide has a low melting point, it acts as a lubricant during cutting and can suppress the adhesion of the cut material.

[0181] When M is silicon, the structure of the third cell layer 17 is refined, thereby improving the hardness and oxidation resistance of the third cell layer 17 , and as a result, improving the hardness and oxidation resistance of the entire coating 3 .

[0182] In addition, "by Al d Cr 1-d-e M e N structure" means that as long as the effect of the present disclosure is exhibited, d Cr 1-d-e M eIn addition to N, it may also contain inevitable impurities. Examples of the inevitable impurities include oxygen and carbon. The overall content of the inevitable impurities in each of the first unit layer 12 and the third unit layer 17 is preferably greater than 0 atomic % and less than 1 atomic %. Here, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms of the constituent layers. The ratio (%) of the number of atoms to the total number of atoms of the constituent layers is calculated by the same method as the above-mentioned "measurement method of a and b". In addition, it was confirmed that as long as the measurement is performed in the same cutting tool 1, there is no deviation in the measurement result even if the measurement site is arbitrarily selected.

[0183] This d is 0.40 or more and 0.75 or less. As a result, the third cell layer 15 has a higher hardness due to the crystal structure of the third cell layer 15 becoming a cubic crystal, and as a result, the “wear resistance” of the third cell layer 15 is improved.

[0184] The d is preferably 0.50 or more, more preferably 0.55 or more, and further preferably 0.60 or more. The c is preferably 0.75 or less, more preferably 0.70 or less, and further preferably 0.65 or less. The c is preferably 0.50 or more and 0.75 or less, more preferably 0.55 or more and 0.70 or less, and further preferably 0.60 or more and 0.65 or less.

[0185] The value of e is greater than 0 and less than 0.05. Thus, the hardness of the first layer 13, 13' and the oxidation resistance of the first layer 13, 13' can be improved. The value of e is preferably greater than 0.002, more preferably greater than 0.005, and further preferably greater than 0.01. The value of e is preferably less than 0.04, more preferably less than 0.03, and further preferably less than 0.02. The value of e is preferably greater than 0.002 and less than 0.05, more preferably greater than 0.005 and less than 0.03, and further preferably greater than 0.01 and less than 0.02.

[0186] The above d and the above e are obtained by the same method as the above “measurement method of a and b”. In addition, it was confirmed that as long as the measurement is performed on the same cutting tool 1, there is no variation in the measurement result even if the measurement position is arbitrarily selected.

[0187] The above-mentioned a and the above-mentioned d satisfy the relationship of d>a. Thereby, the “heat resistance” and “oxidation resistance” of the coating 3 can be improved.

[0188] (Average thickness of the first unit layer and average thickness of the third unit layer)

[0189] The average thickness of the first unit layer 12 is preferably 0.002 μm or more and 0.2 μm or less, and the average thickness of the third unit layer 17 is preferably 0.002 μm or more and 0.2 μm or less. Thus, the progress of cracks generated on the surface of the coating 3 can be further suppressed. The lower limit of the average thickness of the first unit layer 12 is preferably 0.002 μm or more, more preferably 0.005 μm or more, and more preferably 0.01 μm or more. The upper limit of the average thickness of the first unit layer 12 is preferably 0.2 μm or less, more preferably 0.15 μm or less, and more preferably 0.1 μm or less. The average thickness of the first unit layer 12 is more preferably 0.005 μm or more and 0.15 μm or less, and more preferably 0.01 μm or more and 0.1 μm or less. The lower limit of the average thickness of the third unit layer 17 is preferably 0.002 μm or more, more preferably 0.005 μm or more, and more preferably 0.01 μm or more. The upper limit of the average thickness of the third unit layer 17 is preferably 0.2 μm or less, more preferably 0.15 μm or less, and further preferably 0.1 μm or less. The average thickness of the third unit layer 17 is more preferably 0.005 μm to 0.15 μm, and further preferably 0.01 μm to 0.1 μm.

[0190] The average thickness of the first unit layer 12 and the average thickness of the third unit layer 17 can be determined by the same method as the method for measuring the thickness of the above-mentioned 1A layers 13 and 13 ′.

[0191] In the first unit layer 12 and the third unit layer 17 adjacent to the first unit layer 12, the ratio λ3 / λ1 of the thickness λ3 of the third unit layer 17 to the thickness λ1 of the first unit layer 12 is preferably 1 or more and 5 or less ( Figure 5 ). Since the "thermal conductivity" of the third unit layer 17 is low, the third unit layer 17 has the property of being difficult to transfer the heat generated during cutting to the substrate 2. Therefore, if the proportion of the third unit layer 17 in the 1A layer 13, 13' is relatively increased, the amount of Al in the coating 3 increases, thereby improving the thermal blocking property (in other words, "heat resistance") of the cutting tool 1 as a whole, so that the "wear resistance" can also be improved, especially in cutting processing performed under conditions of high tip temperature. λ3 / λ1 is preferably greater than 1, more preferably greater than 1.5, and further preferably greater than 2. λ3 / λ1 is preferably less than 5, more preferably less than 4, and further preferably less than 3. λ3 / λ1 is preferably greater than 1 and less than 5, more preferably greater than 1.5 and less than 4, and further preferably greater than 2 and less than 3.

[0192] In the 1A layers 13 and 13', the stacking numbers of the first unit layer 12 and the third unit layer 17 are preferably 10 or more and 500 or less. As a result, there is a tendency to easily obtain the effect of "balanced improvement of hardness and compressive residual stress by stacking the first unit layer 12 and the third unit layer 17". In the 1A layers 13 and 13', the stacking numbers of the first unit layer 12 and the third unit layer 17 are more preferably 100 or more and 400 or less, and further preferably 200 or more and 350 or less.

[0193] In the 1A layers 13 and 13 ′, the stacking numbers of the first unit layers 12 and the third unit layers 17 can be determined by the same method as the above-mentioned “stacking numbers of the first unit layers 12 and the second unit layers 15 ”.

[0194] <Second Floor>

[0195] The coating 3 further includes a second layer 16 disposed between the substrate 2 and the 1A layer 13, 13'. The composition of the second layer 16 is preferably the same as the composition of the first unit layer 12 or the composition of the third unit layer 17 ( Figure 3 as well as Figure 4 ). Thus, the adhesion between the substrate 2 and the coating 3 can be improved.

[0196] Furthermore, when the composition of the second layer 16 is the same as that of the first unit layer 12 , even if the substrate 2 is exposed at the initial stage of cutting, oxidation at the interface between the substrate 2 and the coating 3 can be suppressed.

[0197] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is preferably thicker than that of the first unit layer 12. Thus, the close contact between the substrate 2 and the coating 3 can be further improved. In addition, even if the substrate 2 is exposed at the initial stage of cutting, oxidation from the interface between the substrate 2 and the coating 3 can be further suppressed. In addition, "the thickness of the second layer 16 is thicker than the thickness of the first unit layer 12" can be said to be "the thickness of the second layer 16 exceeds 1.0 times the thickness of the first unit layer 12". The thickness of the second layer 16 is preferably 2.0 times or more of the thickness of the first unit layer 12, more preferably 4.0 times or more, and further preferably 10.0 times or more. The thickness of the second layer 16 is preferably 500 times or less of the thickness of the first unit layer 12, more preferably 120 times or less, and further preferably 50 times or less. The thickness of the second layer 16 is preferably 2.0 times or more and 500 times or less, more preferably 4.0 times or more and 120 times or less, and further preferably 10.0 times or more and 50 times or less, the thickness of the first unit layer 12 .

[0198] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is preferably 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it tends to be difficult to obtain the effect of suppressing oxidation from the interface between the substrate 2 and the coating 3 by setting the second layer 16 to the same composition as the first unit layer 12. When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 is more preferably 0.3 μm or more, and further preferably 0.4 μm or more. In addition, the upper limit of the thickness of the second layer 16 is not particularly limited, but if it is greater than 2 μm, there is a tendency that the above-mentioned oxidation suppression effect cannot be further improved. Therefore, considering the cost aspect, the thickness of the second layer 16 is preferably 2 μm or less.

[0199] When the composition of the second layer 16 is the same as that of the first unit layer 12, the first unit layer 12 of the 1A layer 13, 13' can be stacked immediately above the second layer 16 having the same composition as that of the first unit layer 12. Figure 4 ), and in addition, a second unit layer 15 ( Figure 3 ). In addition, when the composition of the second layer 16 is the same as that of the first unit layer 12, and the first unit layer 12 of the 1A layer 13, 13' is stacked immediately above the second layer 16, the second layer 16 and the first unit layer 12 of the 1A layer 13, 13' have a continuous crystal structure.

[0200] When the composition of the second layer 16 is the same as that of the third unit layer 17, the third unit layer 17 tends to have a small stress, so the peeling resistance of the coating 3 can be improved, especially in intermittent processing such as milling and end milling where loads are repeatedly applied to the tool tip.

[0201] When the composition of the second layer 16 is the same as that of the third unit layer 17, the thickness of the second layer 16 is preferably thicker than that of the third unit layer 17. As a result, the peeling resistance of the coating 3 can be further improved, especially in intermittent processing such as milling processing and end mill processing in which a load is repeatedly applied to the tool tip. In addition, "the thickness of the second layer 16 is thicker than the thickness of the third unit layer 17" can be said to be "the thickness of the second layer 16 exceeds 1.0 times the thickness of the third unit layer 17". The thickness of the second layer 16 is preferably 2.0 times or more, more preferably 4.0 times or more, and further preferably 10.0 times or more of the thickness of the third unit layer 17. The thickness of the second layer 16 is preferably 500 times or less, more preferably 120 times or less, and further preferably 50 times or less of the thickness of the third unit layer 17. The thickness of the second layer 16 is preferably 2.0 times or more and 500 times or less, more preferably 4.0 times or more and 120 times or less, and further preferably 10.0 times or more and 50 times or less, the thickness of the third unit layer 17 .

[0202] When the composition of the second layer 16 is the same as that of the third unit layer 17, the thickness of the second layer 16 is preferably 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it tends to be difficult to obtain the effect of improving the peeling resistance by setting the second layer 16 to the same composition as the third unit layer 17. When the composition of the second layer 16 is the same as that of the third unit layer 17, the thickness of the second layer 16 is more preferably 0.3 μm or more, and further preferably 0.4 μm or more. In addition, the upper limit of the thickness of the second layer 16 is not particularly limited, but if it is greater than 2 μm, there is a tendency that the above-mentioned further improvement in peeling resistance cannot be confirmed. Therefore, considering the cost aspect, the thickness of the second layer 16 is preferably 2 μm or less.

[0203] When the composition of the second layer 16 is the same as that of the third unit layer 17, the first unit layer 12 of the 1A layer 13, 13' can be stacked immediately above the second layer 16 having the same composition as that of the third unit layer 17. Figure 4 ), and in addition, a third unit layer 17 ( Figure 3 ). In addition, when the composition of the second layer 16 is the same as that of the third unit layer 17, and the third unit layer 17 of the 1A layer 13, 13' is stacked immediately above the second layer 16, the second layer 16 and the third unit layer 17 of the 1A layer 13, 13' have a continuous crystal structure.

[0204] [Embodiment 3: Method for manufacturing cutting tool]

[0205] In Embodiment 3, a method for manufacturing a cutting tool of Embodiment 1 or Embodiment 2 is described. The manufacturing method includes a first step of preparing a substrate and a second step of forming a coating on the substrate. The second step includes a step of forming a first layer or a 1A layer. The details of each step are described below.

[0206] The First Process

[0207] In the first step, a substrate is prepared. As the substrate, the substrate described in Embodiment 1 can be used.

[0208] For example, when cemented carbide is used as a substrate, a commercially available substrate can be used, or it can be manufactured by a general powder metallurgy method. When manufactured by a general powder metallurgy method, for example, WC powder and Co powder are mixed to obtain a mixed powder by a ball mill, etc. After the mixed powder is dried, it is formed into a predetermined shape to obtain a formed body. Further, by sintering the formed body, a WC-Co based cemented carbide (sintered body) is obtained. Then, by subjecting the sintered body to predetermined tool tip processing such as honing, a substrate consisting of a WC-Co based cemented carbide can be manufactured. Even if it is a substrate other than the above, as long as it is a substrate known in the past as such a substrate, all can be prepared.

[0209] Second Process

[0210] In the second step, a coating is formed on the substrate. The second step includes a step of forming the first layer or the 1A layer.

[0211] In the "step of forming the first layer", the first layer is formed by alternately stacking the first unit layer and the second unit layer using a physical vapor deposition (PVD) method. In addition, in the "step of forming the 1A layer", the 1A layer is formed by alternately stacking the first unit layer and the third unit layer using a PVD method. In order to improve the wear resistance of the coating including the first layer or the 1A layer, it is preferred to form a layer composed of a highly crystalline compound. The inventors of the present invention have studied various methods as a method for forming the first layer and the 1A layer, and found that the physical vapor deposition method is preferably used.

[0212] As the PVD method, at least one selected from the group consisting of cathode arc ion plating, balanced magnetron sputtering, unbalanced magnetron sputtering, and HiPIMS can be used. It is particularly preferred to use a cathode arc ion plating method with a high ionization rate of the raw material element. When the cathode arc ion plating method is used, before forming the first layer, the surface of the substrate can be subjected to a metal ion bombardment treatment, so that the adhesion between the substrate and the coating film including the first layer is significantly improved.

[0213] Cathodic arc ion plating can be performed, for example, by placing a substrate in an apparatus and a target as a cathode, applying a high voltage to the target to generate arc discharge, thereby ionizing and evaporating atoms constituting the target, and depositing a substance on the substrate.

[0214] The balanced magnetron sputtering method can be carried out, for example, as follows: a target is set on a magnetron electrode having a magnet that sets a substrate in the device and forms a balanced magnetic field, high-frequency power is applied between the magnetron electrode and the substrate to generate gas plasma, and gas ions generated by the generation of the gas plasma collide with the target, so that atoms released from the target are deposited on the substrate.

[0215] The unbalanced magnetron sputtering method can be performed by making the magnetic field generated by the magnetron electrodes in the above-mentioned balanced magnetron sputtering method unbalanced, for example. Furthermore, the HiPIMS method can be used, which can apply a high voltage to obtain a dense film.

[0216] <Other Processes>

[0217] The above-mentioned second process may further include surface treatment processes such as surface grinding and shot peening on the basis of the above-mentioned "process of forming the first layer or the 1A layer". In addition, the above-mentioned second process may further include processes of forming other layers (base layer (second layer), intermediate layer, surface layer (third layer), etc.) on the basis of the above-mentioned "process of forming the first layer or the 1A layer". In the case where the coating includes other layers (base layer (second layer), intermediate layer, surface layer (third layer), etc.), these layers can be formed by conventionally known methods. These other layers can be formed by conventionally known chemical vapor deposition methods and physical vapor deposition methods. From the viewpoint of being able to form other layers continuously with the first unit layer, the second unit layer or the third unit layer in one physical vapor deposition device, the other layers are preferably formed by physical vapor deposition methods.

[0218] Example

[0219] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.

[0220] [Example 1]

[0221] 《Manufacturing of cutting tools》

[0222] <Production of Cutting Tools Concerning Samples 1-1 to 1-24, 1-27, 1-28, and 1-101 to 1-110>

[0223] (First step: step of preparing a substrate)

[0224] Figure 6 is a schematic cross-sectional view of the cathode arc ion plating device used in this embodiment, Figure 7yes Figure 6 A schematic top view of the device.

[0225] exist Figure 6 as well as Figure 7 In the device, a cathode 106 for the first unit layer, a cathode 107 for the second unit layer, and a cathode 120 for the third layer, which are targets made of alloys of metal raw materials to be coated, and a rotatable substrate holder 104 for setting the substrate 2 are installed in the chamber 101. An arc power supply 108 is installed in the cathode 106, and an arc power supply 109 is installed in the cathode 107. In addition, a bias power supply 110 is installed in the substrate holder 104. In addition, a gas inlet for introducing a gas 105 is provided in the chamber 101, and a gas exhaust port 103 is provided in order to adjust the pressure in the chamber 101, so that the gas in the chamber 101 can be sucked from the gas exhaust port 103 by a vacuum pump.

[0226] On the substrate holder 104 , as the substrate 2 , a cutting insert of a JIS P30 grade cemented carbide having a shape of JIS CNMG120408 and a cutting insert of SEMT13T3AGSN manufactured by Sumitomo Electric Hardmetal Co., Ltd. are mounted.

[0227] Next, the pressure in the chamber 101 was reduced by a vacuum pump, and the temperature was heated to 500° C. by a heater installed in the apparatus while the substrate 2 was rotated, and the chamber 101 was evacuated until the pressure in the chamber 101 reached 1.0×10 -4 Then, argon gas was introduced from the gas inlet, the pressure in the chamber 101 was maintained at 2.0 Pa, the voltage of the bias power supply 110 was gradually increased to -1000 V, and the surface of the substrate 2 was cleaned for 15 minutes. After that, the substrate was cleaned by exhausting argon gas from the chamber 101 (argon bombardment treatment). Through the above, the substrates of the cutting tools involved in the samples 1-1 to 1-24, 1-27, 1-28, and 1-101 to 1-110 were prepared.

[0228] (Second step: step of forming a coating on a substrate)

[0229] Next, while the substrate 2 was rotated at the center, nitrogen gas was introduced as a reaction gas, and while the temperature of the substrate 2 was maintained at 500°C, the reaction gas pressure was maintained at 2.0 Pa, and the voltage of the bias power supply 110 was maintained at a constant value in the range of -50V to -200V, an arc current of 120A was supplied to the cathode 106 and the cathode 107, respectively, thereby generating metal ions from the cathode 106 and the cathode 107, and forming the second layer and the first layer having the composition shown in Table 1 and Table 2 on the substrate. In addition, the composition of the cathode 106 was adjusted so that the ratio of Ti, Al, and Ce was the same as the ratio of the composition of the first unit layer in Table 1 and Table 2. In addition, the composition of the cathode 107 was adjusted so that the ratio of Cr and Al was the same as the ratio of the composition of the second unit layer in Table 1 and Table 2.

[0230] In the case where the second layer is formed, the first layer is formed by alternately stacking the first unit layer and the second unit layer on the second layer by the number of stacking layers shown in Table 1 and Table 2, respectively. In the case where the second layer is not formed, the first layer is formed by alternately stacking the first unit layer and the second unit layer on the substrate by the number of stacking layers shown in Table 1 and Table 2, respectively. In addition, the thickness of the second layer, the thickness of each of the first unit layer and the second unit layer in the first layer, and the number of stacking layers are adjusted by the rotation speed of the substrate. Then, when the thickness of the second layer and the first layer reaches the thickness shown in Table 1 and Table 2, respectively, the current supplied to the evaporation source is stopped.

[0231] Next, while introducing nitrogen and methane as reaction gases into the chamber 101, an arc current of 100A is supplied to the cathode 120 while maintaining the temperature of the substrate 2 at 400°C, the reaction gas pressure at 2.0Pa, and the voltage of the bias power supply 110 at -300V, thereby generating metal ions from the cathode 120 and forming the third layer on the first layer. When the thickness of the third layer reaches the thickness shown in Tables 1 and 2, the current supplied to the evaporation source is stopped. In addition, the composition of the cathode 120 is adjusted in such a way that the ratio of Ti, Al, and Ce is the same as the ratio of the composition of the third layer in Tables 1 and 2. In addition, the ratio of nitrogen to carbon in the composition of the third layer is adjusted according to the ratio of the amount of nitrogen introduced to the amount of methane introduced. Through the above, cutting tools involving samples 1-1 to 1-24, 1-27, 1-28, and 1-101 to 1-110 were produced.

[0232]

[0233]

[0234] "evaluate"

[0235] For the cutting tools involved in each sample, the composition of the first unit layer (i.e., a and b), the composition of the second unit layer (i.e., c), the composition of the second layer, the composition of the third layer, the number of layers, the average thickness of the first unit layer, the average thickness of the second unit layer, the thickness of the first layer, the thickness of the second layer, the thickness of the third layer and λ2 / λ1 were measured.

[0236] <Measurement of Composition (a and b) of First Unit Layer>

[0237] For the cutting tool of each sample, the above-mentioned a was obtained by the method described in Implementation Example 1. The obtained results are recorded in the "a" column of Table 1 and Table 2, respectively. In addition, for the cutting tool of each sample, the above-mentioned b was obtained by the method described in Implementation Example 1. The obtained results are recorded in the "b" column of Table 1 and Table 2, respectively. In addition, in Table 1 and Table 2, when "-" is recorded in the "a" column and the "b" column, it means that the first unit layer does not exist.

[0238] <Measurement of Composition (c) of Second Unit Layer>

[0239] For each sample cutting tool, the above c was obtained by the method described in Embodiment 1. The obtained results are recorded in the "c" column of Table 1 and Table 2. In Table 1 and Table 2, when "-" is recorded in the "c" column, it means that the second unit layer does not exist.

[0240] <Measurement of Composition of Second Layer and Composition of Third Layer>

[0241] For the cutting tools of each sample, the composition of the second layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Composition" column of the "Second Layer" column in Table 1 and Table 2, respectively. In addition, for the cutting tools of each sample, the composition of the third layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Composition" column of the "Third Layer" column in Table 1 and Table 2, respectively. In addition, when the "Composition" column in the "Second Layer" column in Table 1 and Table 2 is recorded as "-", it means that the second layer does not exist, and when the "Composition" column in the "Third Layer" column in Table 1 and Table 2 is recorded as "-", it means that the third layer does not exist.

[0242] <Determination of the number of layers>

[0243] The above-mentioned number of stacking was obtained for the cutting tool of each sample by the method described in Embodiment 1. The obtained results are described in the column of "Number of stacking" in Tables 1 and 2, respectively.

[0244] <Measurement of Average Thickness of First Unit Layer, Average Thickness of Second Unit Layer, Thickness of First Layer, Thickness of Second Layer, and Thickness of Third Layer>

[0245] For the cutting tools of each sample, the average thickness of the first unit layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Average Thickness [μm]" column in the "First Unit Layer" column of Table 1 and Table 2, respectively. In addition, for the cutting tools of each sample, the average thickness of the second unit layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Average Thickness [μm]" column in the "Second Unit Layer" column of Table 1 and Table 2, respectively. In addition, for the cutting tools of each sample, the thickness of the first layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "First Layer" column of Table 1 and Table 2, respectively. In addition, for the cutting tools of each sample, the thickness of the second layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "Second Layer" column of Table 1 and Table 2, respectively. In addition, for the cutting tools of each sample, the thickness of the third layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "Third Layer" column of Table 1 and Table 2, respectively. In addition, when the "Average Thickness [μm]" column in the "First Unit Layer" column of Table 1 and Table 2 is recorded as "-", it means that the first unit layer does not exist. When the "Average Thickness [μm]" column in the "Second Unit Layer" column of Table 1 and Table 2 is recorded as "-", it means that the second unit layer does not exist. When the "Thickness [μm]" column in the "Second Layer" column of Table 1 and Table 2 is recorded as "-", it means that the second layer does not exist. When the "Thickness [μm]" column in the "Third Layer" column of Table 1 and Table 2 is recorded as "-", it means that the third layer does not exist.

[0246] <Measurement of λ2 / λ1>

[0247] For the cutting tool of each sample, the above-mentioned λ2 / λ1 was obtained by the method described in Embodiment 1. The obtained results are recorded in the "λ2 / λ1" column of Table 1 and Table 2. In addition, when "-" is recorded in the "λ2 / λ1" column of Table 1 and Table 2, it means that at least one of the first unit layer and the second unit layer does not exist.

[0248] <Cutting tool life evaluation>

[0249] (Cutting test 1: continuous turning test)

[0250] For the CNMG120408-shaped cutting tools of samples 1-1 to 1-24, 1-27, 1-28, 1-101 to 1-110, a dry continuous turning test was performed under the following cutting conditions, and the time until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting time [minutes]" column of Tables 1 and 2. In addition, in Tables 1 and 2, a long cutting time means a long tool life.

[0251] (Cutting conditions)

[0252] ·Material to be cut: SCM440 (HB=300)

[0253] Cutting speed: 250m / min

[0254] Feed speed: 0.3mm / rev

[0255] ·Incision: 2.0mm

[0256] Coolant: Dry

[0257] The cutting process performed under the above-mentioned cutting conditions is high-speed and high-efficiency machining of difficult-to-cut materials, and is equivalent to cutting processing performed under the condition of high tool tip temperature.

[0258] It was confirmed that the cutting tools involved in samples 1-1 to 1-24, 1-27, and 1-28 had significantly lower flank wear of the tool tip in the continuous turning test than the cutting tools involved in samples 1-101 to 1-110. In other words, it was confirmed that the cutting tools involved in samples 1-1 to 1-24, 1-27, and 1-28 had longer tool life than the cutting tools involved in samples 1-101 to 1-110, especially in cutting processes performed under conditions of high tool tip temperatures.

[0259] (Cutting test 2: Milling test)

[0260] For the SEMT13T3AGSN cutting tools of samples 1-1 to 1-24, 1-27, 1-28, 1-101 to 1-110, the center line of a plate with a width of 150 mm made of a difficult-to-cut material and a width greater than the center line of the plate with a width of 150 mm were aligned. The cutter was aligned at the center of the cutter, and surface milling was performed under the following cutting conditions (i.e., a dry milling test was performed), and the cutting length until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting Length [km]" column of Tables 1 and 2. In addition, in Tables 1 and 2, a longer cutting length means a longer tool life.

[0261] (Cutting conditions)

[0262] ·Material to be cut: SKD11 (HB=235)

[0263] Cutting speed: 180m / min

[0264] Feed speed: 0.15mm / t

[0265] Axial incision ap: 1.5mm

[0266] Radial cut ae: 150mm

[0267] Coolant: Dry

[0268] The cutting process performed under the above-mentioned cutting conditions is a high-speed and high-efficiency milling process of difficult-to-cut materials under dry conditions, which is equivalent to a cutting process performed under conditions where the tool tip temperature is high.

[0269] It was confirmed that the cutting length of the cutting edge of the cutting tools of samples 1-1 to 1-24, 1-27, and 1-28 was significantly increased compared to the cutting tools of samples 1-101 to 1-110. In other words, it was confirmed that the cutting tools of samples 1-1 to 1-24, 1-27, and 1-28 had a longer tool life than the cutting tools of samples 1-101 to 1-110, especially in cutting processes performed under conditions of high cutting edge temperature.

[0270] [Example 2]

[0271] 《Manufacturing of cutting tools》

[0272] <Production of Cutting Tools Concerning Samples 2-1 to 2-19 and 2-101 to 2-110>

[0273] The cutting tools involved in samples 2-1 to 2-19 and 2-101 to 2-110 were prepared by the same method as the cutting tools involved in the above-mentioned samples 1-1 to 1-24, 1-27, 1-28, and 1-101 to 1-110, except for the following aspects: In the second step, "a second layer and a "1A layer" having the composition shown in "Table 3 and Table 4" are formed on the substrate. In addition, the composition of the cathode 106 is adjusted in a manner such that the ratio of Ti, Al, and Ce is the same as the ratio of the composition of the first unit layer in "Table 3 and Table 4". In addition, the composition of the cathode 107 is adjusted in a manner such that the ratio of Cr, Al, "Si, and B" is the same as the ratio of the composition of the "third unit layer" in "Table 3 and Table 4". In addition, in the second step, "when the second layer is formed, the "1A layer" is formed. "A layer" is formed by alternately stacking the first unit layer and the "third unit layer" on the second layer by the number of stacking layers shown in "Table 3 and Table 4". In the case where the second layer is not formed, the "1A layer" is formed by alternately stacking the first unit layer and the "third unit layer" on the substrate by the number of stacking layers shown in "Table 3 and Table 4". "When the thickness of the second layer and the "1A layer" reaches the thickness shown in "Table 3 and Table 4", respectively, the current supplied to the evaporation source is stopped." "When the thickness of the third layer reaches the thickness shown in "Table 3 and Table 4", the current supplied to the evaporation source is stopped. In addition, the composition of the cathode 120 is adjusted in a manner such that the ratio of Ti, Al, and Ce is the same as the ratio of the composition of the third layer in "Table 3 and Table 4".

[0274]

[0275]

[0276] "evaluate"

[0277] For the cutting tools involved in each sample, the composition of the first unit layer (i.e., a and b), the composition of the third unit layer (i.e., d and e), the composition of the second layer, the composition of the third layer, the number of stacking layers, the average thickness of the first unit layer, the average thickness of the third unit layer, the thickness of the 1A layer, the thickness of the second layer, the thickness of the third layer and λ3 / λ1 were measured.

[0278] <Measurement of Composition (a and b) of First Unit Layer>

[0279] For the cutting tools of each sample, the above-mentioned a was obtained by the method described in Embodiment 1. The obtained results are respectively recorded in the "a" column of Table 3 and Table 4. In addition, for the cutting tools of each sample, the above-mentioned b was obtained by the method described in Embodiment 1. The obtained results are respectively recorded in the "b" column of Table 3 and Table 4.

[0280] <Measurement of Composition (d and e) of Second Unit Layer>

[0281] For the cutting tools of each sample, the above d was obtained by the method described in Embodiment 2. The obtained results are recorded in the "d" column of Table 3 and Table 4, respectively. In addition, for the cutting tools of each sample, the above e was obtained by the method described in Embodiment 2. The obtained results are recorded in the "e" column of Table 3 and Table 4, respectively. In addition, in Table 3 and Table 4, when "-" is recorded in the "d" column and the "e" column, it means that the third unit layer does not exist.

[0282] <Measurement of Composition of Second Layer and Composition of Third Layer>

[0283] For the cutting tools of each sample, the composition of the second layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Composition" column in the "Second Layer" column of Tables 3 and 4, respectively. In addition, for the cutting tools of each sample, the composition of the third layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Composition" column in the "Third Layer" column of Tables 3 and 4, respectively. In addition, when the "Composition" column in the "Second Layer" column of Tables 3 and 4 is recorded as "-", it means that the second layer does not exist, and when the "Composition" column in the "Third Layer" column of Tables 3 and 4 is recorded as "-", it means that the third layer does not exist.

[0284] <Determination of the number of layers>

[0285] The above-mentioned number of stacking was obtained for the cutting tool of each sample by the method described in Embodiment 2. The obtained results are described in the column of "Number of stacking" in Tables 3 and 4, respectively.

[0286] <Measurement of Average Thickness of First Unit Layer, Average Thickness of Third Unit Layer, Thickness of 1A Layer, Thickness of Second Layer, and Thickness of Third Layer>

[0287] For the cutting tools of each sample, the average thickness of the first unit layer was determined by the method described in Implementation Example 2. The obtained results are recorded in the "Average Thickness [μm]" column in the "First Unit Layer" column of Tables 3 and 4, respectively. In addition, for the cutting tools of each sample, the average thickness of the third unit layer was determined by the method described in Implementation Example 2. The obtained results are recorded in the "Average Thickness [μm]" column in the "Third Unit Layer" column of Tables 3 and 4, respectively. In addition, for the cutting tools of each sample, the thickness of the 1A layer was determined by the method described in Implementation Example 2. The obtained results are recorded in the "Thickness [μm]" column in the "1A Layer" column of Tables 3 and 4, respectively. In addition, for the cutting tools of each sample, the thickness of the second layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column in the "Second Layer" column of Tables 3 and 4, respectively. In addition, for the cutting tools of each sample, the thickness of the third layer was determined by the method described in Implementation Example 1. The obtained results are recorded in the "Thickness [μm]" column of the "Third Layer" column in Tables 3 and 4, respectively. In addition, when the "Average Thickness [μm]" column in the "First Unit Layer" column in Tables 3 and 4 is recorded as "-", it means that the first unit layer does not exist. When the "Average Thickness [μm]" column in the "Third Unit Layer" column in Tables 3 and 4 is recorded as "-", it means that the third unit layer does not exist. When the "Thickness [μm]" column in the "Second Layer" column in Tables 3 and 4 is recorded as "-", it means that the second layer does not exist. When the "Thickness [μm]" column in the "Third Layer" column in Tables 3 and 4 is recorded as "-", it means that the third layer does not exist.

[0288] <Measurement of λ3 / λ1>

[0289] For the cutting tool of each sample, the above-mentioned λ3 / λ1 was obtained by the method described in Embodiment 2. The obtained results are recorded in the "λ3 / λ1" column of Table 3 and Table 4. In addition, when "-" is recorded in the "λ3 / λ1" column of Table 3 and Table 4, it means that at least one of the first unit layer and the third unit layer does not exist.

[0290] <Cutting tool life evaluation>

[0291] (Cutting test 3: continuous turning test)

[0292] For the CNMG120408-shaped cutting tools of samples 2-1 to 2-19 and 2-101 to 2-110, a dry continuous turning test was performed under the following cutting conditions, and the time until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting time [minutes]" column of Tables 3 and 4. In addition, in Table 2, a long cutting time means a long tool life.

[0293] (Cutting conditions)

[0294] ·Material to be cut: Inconel 718 (aging material: HB = 400)

[0295] Cutting speed: 65m / min

[0296] Feed speed: 0.15mm / rev

[0297] ·Incision: 1.0mm

[0298] Coolant: Dry

[0299] The cutting process performed under the above-mentioned cutting conditions is high-speed and high-efficiency machining of difficult-to-cut materials, and is equivalent to cutting processing performed under the condition of high tool tip temperature.

[0300] It was confirmed that the cutting tools involved in samples 2-1 to 2-19 had significantly lower flank wear of the tool tip in the continuous turning test than the cutting tools involved in samples 2-101 to 2-110. In other words, it was confirmed that the cutting tools involved in samples 2-1 to 2-19 had longer tool life, especially in cutting processes performed under conditions of high tool tip temperatures, than the cutting tools involved in samples 2-101 to 2-110.

[0301] (Cutting test 4: Milling test)

[0302] For the SEMT13T3AGSN cutting tools of samples 2-1 to 2-19 and 2-101 to 2-110, the center line of a plate with a width of 150 mm made of a difficult-to-cut material and a plate with a width greater than the center line of the ... The cutter was aligned at the center of the cutter, and surface milling was performed under the following cutting conditions (i.e., a dry milling test was performed), and the cutting length until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting Length [km]" column of Tables 3 and 4. In addition, in Table 2, a long cutting length means a long tool life.

[0303] (Cutting conditions)

[0304] ·Material to be cut: FCD700 (HB=250)

[0305] Cutting speed: 250m / min

[0306] Feed speed: 0.2mm / t

[0307] Axial incision ap: 2.0mm

[0308] Radial cut ae: 150mm

[0309] Coolant: Dry

[0310] The cutting process performed under the above-mentioned cutting conditions is a high-speed and high-efficiency milling process of difficult-to-cut materials under dry conditions, which is equivalent to a cutting process performed under conditions where the tool tip temperature is high.

[0311] It was confirmed that the cutting length of the cutting edge of the cutting tools of samples 2-1 to 2-19 was significantly increased compared with the cutting tools of samples 2-101 to 2-110. In other words, it was confirmed that the cutting tools of samples 2-1 to 2-19 had a longer tool life, especially in cutting processing performed under conditions of high cutting edge temperature, compared with the cutting tools of samples 2-101 to 2-110.

[0312] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.

[0313] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.

[0314] Description of Reference Numerals

[0315] 1: cutting tool; 2: substrate; 3: coating; 12: first unit layer; 13, 13': first layer, 1A layer; 14: third layer; 15: second unit layer; 16: second layer; 17: third unit layer; 101: chamber; 103: gas outlet; 104: substrate holder; 105: gas; 106, 107, 120: cathode; 108, 109: arc power supply; 110: bias power supply.

Claims

1. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises a first layer, The first layer is composed of alternating layers formed by alternatingly stacking first unit layers and second unit layers, The first unit layer is made of Ti 1-a-b Al a Ce b N constitutes, a is greater than or equal to 0.350 and less than or equal to 0.650, The b is greater than or equal to 0.001 and less than or equal to 0.100, The second unit layer is composed of Al c Cr 1-c N constitutes, The c is greater than or equal to 0.40 and less than or equal to 0.75, The a and the c satisfy the relationship c>a.

2. The cutting tool according to claim 1, wherein: In the first unit layer and the second unit layer adjacent to the first unit layer, a ratio λ2 / λ1 of a thickness λ2 of the second unit layer to a thickness λ1 of the first unit layer is 1 or more and 5 or less.

3. The cutting tool according to claim 1 or 2, wherein: The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm, The average thickness of the second unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.

4. The cutting tool according to any one of claims 1 to 3, wherein: The coating further includes a second layer disposed between the substrate and the first layer. The composition of the second layer is the same as the composition of the first unit layer or the composition of the second unit layer.

5. The cutting tool according to claim 4, wherein: The composition of the second layer is the same as that of the first unit layer, The second layer is thicker than the first unit layer.

6. The cutting tool according to claim 4, wherein: The composition of the second layer is the same as the composition of the second unit layer, The second layer has a thickness greater than that of the second unit layer.

7. The cutting tool according to any one of claims 1 to 6, wherein: The coating further includes a third layer disposed on a side of the first layer opposite to the substrate. The third layer is composed of TiAlCeCN.

8. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises a layer 1A, The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked. The first unit layer is made of Ti 1-a-b Al a Ce b N constitutes, a is greater than or equal to 0.350 and less than or equal to 0.650, The b is greater than or equal to 0.001 and less than or equal to 0.100, The third unit layer is composed of Al d Cr 1-d-e M e N constitutes, The M is silicon or boron, The d is greater than or equal to 0.40 and less than or equal to 0.75, The e is greater than 0 and less than 0.05, The a and the d satisfy the relationship of d>a.

9. The cutting tool according to claim 8, wherein: In the first unit layer and the third unit layer adjacent to the first unit layer, a ratio λ3 / λ1 of a thickness λ3 of the third unit layer to a thickness λ1 of the first unit layer is 1 or more and 5 or less.

10. The cutting tool according to claim 8 or 9, wherein: The M is silicon.

11. The cutting tool according to claim 8 or 9, wherein: The M is boron.

12. The cutting tool according to any one of claims 8 to 11, wherein: The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm, The average thickness of the third unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.

13. The cutting tool according to any one of claims 8 to 12, wherein: The coating further includes a second layer disposed between the substrate and the 1A layer, The composition of the second layer is the same as the composition of the first unit layer or the composition of the third unit layer.

14. The cutting tool according to claim 13, wherein: The composition of the second layer is the same as that of the first unit layer, The second layer is thicker than the first unit layer.

15. The cutting tool according to claim 13, wherein: The composition of the second layer is the same as that of the third unit layer, The second layer is thicker than the third unit layer.

16. The cutting tool according to any one of claims 8 to 15, wherein: The coating further includes a third layer disposed on the side of the 1A layer opposite to the substrate, The third layer is composed of TiAlCeCN.

Citation Information

Patent Citations

  • Nano composite coating and deposition method thereof

    CN104789933A

  • Throw-away insert of surface coated super-hard alloy

    JP1997300105A

  • Cutting tool made of surface coated cubic boron nitride group sintered material with hard coating layer exhibiting excellent chipping resistance in heavy cutting

    JP2005022023A

  • Surface coated cutting tool

    JP2020131425A

  • Surface-coated cutting tool exhibiting excellent chipping resistance and wear resistance in strong intermittent cutting

    JP2021126738A